Democratic Transition and Independence of the Central Bank: The Case of Tunisia - ABBES, Dorra (Theoretical and Practical Research in Economic Fields; Vol 16 No 3 (2025): TPREF, Volume XVI, Issue 3(35), Fall 2025, 2025)
After the revolution, the demands of the Tunisian people in terms of democracy, transparency, and independence of institutions have not stopped. It is in this context that the pressure exerted by the Tunisian parliament to revise the statute of the Central Bank of Tunisia (CBT) to demand more independence. This study aims to assess the degree of independence of the CBT before and after the democratic transition that characterizes the political life of the country. The degree of independence has been assessed according to the calculation of the legal index based on the evolution of the statutes governing the organization and missions of the CBT since its creation. The calculations carried out on the basis of the various statutes made it possible to notice a significant improvement in the degree of independence, and this, in accordance with the theoretical predictions, the more the country tends towards democracy, the more the independence of the Central Bank is required. Overall, the democratic transition has had a favorable effect on the evolution of the degree of independence of the CBT, as evidenced by the improvement recorded in the score in 2016.